The 5-item likert scale and percentage scale correspondence with implications for the use of models with (fuzzy) linguistic variables - Jiérí Mazurek; Cristina Pérez Rico; Carlos Fernández; Jean-Pierre Magnot; Tristan Magnot (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2021)
The aim of this paper is to examine how people perceive correspondence between the 5-item Likert scale and the percentage scale (the LS-PS correspondence thereinafter). Are all five items of the Likert scale equidistant? Do people use the same scale when evaluating different objects? Are men and women different? Are people from different countries / cultures different? The method of the study was a questionnaire with 661 participating respondents altogether from the Czech Republic, Ecuador, and France. The results indicate that the 5-item Likert scale is neither equidistant, nor symmetrical. Furthermore, there are (highly) statistically significant differences in the LS-PS correspondence with respect to location, age, or gender of respondents. The results can be used as an input for more precise decision-making modeling associated with (fuzzy) linguistic variables.
Keywords: D12; D91; 330; decision-making; evaluation; fuzzy linguistic variables; international study; Likert scale